반응표면분석법을 이용한 개조개(Saxidomus purpuratus) 패각분말로부터 가용성 초산칼슘의 제조 및 특성 - 이현지(Hyun Ji Lee); 정남영(Nam Young Jung); 박성환(Sung Hwan Park); 송상목(Sang Mok Song); 강상인(Sang In Kang); 김진수(Jin-Soo Kim); 허민수(Min Soo Heu) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2015)
For effective utilization of butter clam shell as a natural calcium resource, the optimal conditions for preparation of calcium acetate (BCCA) with high solubility were determined using response surface methodology (RSM). The polynomial models developed by RSM for pH, solubility, and yield were highly effective in describing the relationships between factors (P<0.05). Increased molar ratio of calcined powder (BCCP) from butter clam shell led to reduction of solubility, yield, color values, and overall quality. Critical values of multiple response optimization to independent variables were 2.70 M and 1.05 M for acetic acid and BCCP, respectively. The actual values (pH 7.04, 93.0% for solubility and 267.5% for yield) under optimization conditions were similar to predicted values. White indices of BCCAs were in the range of 89.7~93.3. Therefore, color value was improved by calcination and organic acid treatment. Buffering capacity of BCCAs was strong at pH 4.88 to 4.92 upon addition of ~2 mL of 1 N HCl. Calcium content and solubility of BCCAs were 20.7~22.8 g/100 g and 97.2~99.6%, respectively. The patterns of fourier transform infrared spectrometer and X-ray diffractometer analyses from BCCA were identified as calcium acetate monohydrate, and microstructure by field emission scanning electron microscope showed an irregular form. 패류의 주된 가공부산물인 패각은 주성분이 불용성의 탄산 칼슘으로, 이를 천연 칼슘소재로 활용하기 위해 개조개 패각의 소성분말로부터 가용성 개선 유기산(초산) 처리 칼슘 제조의 최적조건을 구명하고자 하였다. 반응표면분석법을 이용하여 제조한 11개의 시제 초산칼슘의 pH, 용해도 및 수율로부터 구명한 최적 반응조건은 초산 2.70 M 비율에 대하여 개조개 소성분말 1.05 M이었으며, 이의 최적조건을 적용한 개조개 초산칼슘의 실측 pH, 용해도 및 수율은 각각 pH 7.04, 93.0% 및 267.5%로 예측치와 유사한 결과를 얻었다. 시제 초산칼슘의 완충능은 pH 4.88~4.92 범위였으며, 칼슘 함량과 용해도는 20.7~22.8 g/100 g과 97.2~99.6%였다. FT-IR, XRD 분석 및 FESEM을 통한 미세구조는 비정형 결정으로 calcium acetate monohydrate로 확인되었다. 개조개 패각은 칼슘소재뿐만 아니라 가용성을 높인 유기산 칼슘으로 칼슘강화용 식품소재로의 이용 가능성이 높을 것으로 판단되었다.